Effect of Salt Content (NaCl) on the Antagonistic Power of Gliocladium sp. in Inhibiting the growth of Fusarium oxysporum f. sp. Cubense Causes Fusarium wilt in Banana Plants - Muhammad Affan (Contributions of Central Research Institute for Agriculture, 2023)
This study aims to determine the effect of salt/salinity (NaCl) levels on the growth of Gliocladium sp. (Colony area, dry weight and number of spores) and antagonistic activity of Gliocladium sp. in inhibiting Foc. The research was conducted at the Laboratory of Plant Diseases, Department of Plant Pests and Diseases, Faculty of Agriculture, University of Brawijaya. The stages in this study included counting colony area, sporulation and dry weight of Gliocladium sp. with single culture method, antagonism test between Gliocladium sp. and Foc with dual culture method. In the research stage to determine the effect of salt levels used NaCl, with concentrations of 0 gr/l, 4 gr/l, 8 gr/l, 12 gr/l and 16 gr/l. The design method used in this study was a completely randomized design (CRD). Banana plants can grow in tropical climates with a pH of 4.5-7. In banana cultivation there are several obstacles that can reduce banana production, the main obstacle is caused by the attack of the pathogen Fusarium oxysporum f. sp cubense (Foc) which causes banana plants to wilt. Efforts to control the attack of pathogenic Foc, can be done by utilizing the antagonistic fungus Gliocladium sp. The results showed that the colony area, sporulation and dry weight of Gliocladium sp. showed that overall growth increased with increasing salt content used, the results obtained were colony area, sporulation and dry weight of Gliocladium sp. The highest yield was found in the treatment with a concentration of salt content of 16 gr/l, with values of 4.184 cm2, 7.933 spores/ml and 0.132 gr respectively, while the antagonism test between Gliocladium sp. and Foc, the highest inhibition percentage of Gliocladium sp. occurred at a salt concentration of 16 gr/l of 45.556%. The research shows that the addition of NaCl to the media has a positive effect on Gliocladium sp.